On Taste as Ethical-aesthetic Notion in Kant - Laiho Hemmo (France, 2025)
It may be that Kant’s inherently communal concept of taste is a morally laden notion that blurs the line between the good and the beautiful, on the one hand, and moral evaluation and aesthetic appreciation, on the other. In particular, it can be shown how, on Kant’s view, moralistic factors, such as considerations of social appropriateness, enter into estimations of aesthetic value. Moreover, Kant’s tendency to overlap taste and morals suggests an underlying assumption operative in Kant’s aesthetics. According to this ‘decency assumption’, as I have termed it, taste is first and foremost a trait of people with certain supposedly refined socio-moral characteristics. Kant also seems to think that having good taste and a morally good character go hand in hand. Even though we do find separate sets of ultimate principles in Kant’s ethics and aesthetics, the aforesaid assumption nevertheless implies a shared ground between these two branches of philosophy and thereby links them tightly together, contrary to the common view that ethics and aesthetics are distinct enterprises. In addition, Kant’s morally laden conception of taste will be shortly examined in relation to the Enlightenment project as Kant saw it and our contemporary world.
12th Kant-Readings International Conference “Kant and the Ethics of Enlightenment: Historical Roots and Contemporary Relevance”